2020
DOI: 10.1002/2050-7038.12363
|View full text |Cite
|
Sign up to set email alerts
|

STA and SOSM control‐based approach of a renewable power generator for adjusting grid frequency and voltage

Abstract: Summary This article is interested in a controlled three‐phased voltage source inverter (VSI) for a grid‐connected wind power generator. The objective consists of participating in auxiliary services by enhancing the grid stability. An active wind generator associated with a battery/super‐capacitor storage system composes the studied renewable generator. It is related to a power consumer (load) to form a microgrid (MG) that can work according to grid stability in two modes: standalone and grid‐tied. Thus, the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…In literature various control schemes are reported for GICs to interface the renewable energy based DGs to the utility grid [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. To ensure good power quality at PCC either additional compensating devices or GICs with multifunctional capabilities shall be utilized [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…In literature various control schemes are reported for GICs to interface the renewable energy based DGs to the utility grid [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. To ensure good power quality at PCC either additional compensating devices or GICs with multifunctional capabilities shall be utilized [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Various control techniques based on PI controller, proportional resonance (PR) controller, sliding mode controller (SMC), model predictive controller (MPC) and intelligent controllers are discussed for regulating power flows and to improve power quality in a grid connected MG (GC-MG) [10][11][12][13][14][15][16][17][18][19][20][21]. In [10], authors have utilized PI controller for integrating renewable energy resources to MG with low THD under ideal conditions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, the authors reported an increase in power factor at the grid side with these techniques, while the THD remained within the IEEE standards. The authors 13 developed a robust control technique for connecting the grid's microgrid (MG) set. The authors analyzed the microgrid control method to operate in the island mode to ensure continuous supply to the distribution station during the grid's failure.…”
Section: Introductionmentioning
confidence: 99%